Job mobility in Europe, Japan and the US - Lex Borghans; Bart H. H. Golsteyn (Institute for the Study of Labor (IZA), 2010)
Evidence about job mobility outside the U.S. is scarce and difficult to compare cross-nationally because of non-uniform data. We document job mobility patterns of college graduates in their first three years in the labor market, using unique uniform data covering 11 European countries and Japan. Using the NLSY, we replicate the information in this survey to compare the results to the U.S. We find that (1) U.S. graduates hold more jobs than European graduates. (2) Contrasting conventional wisdom, job mobility in Japan is only somewhat lower than the European average. (3) There are large differences in job mobility within Europe.
Keywords: J24; J31; I2; 330; job mobility; graduates; Europe; Japan; US